User involvement in digital health: Working together to design smart home health technology. (5th October 2018) - Burrows, Alison; Meller, Ben; Craddock, Ian; Hyland, Fiona; Gooberman‐Hill, Rachael
Abstract: Background: Public involvement adds value to numerous aspects of health research, yet few studies have attempted to evaluate its impact on research. Evidence of such impact is needed to develop recommendations for best practice and ensure adequate resourcing. Aim: To evaluate public involvement within a large interdisciplinary Science, Technology, Engineering and Mathematics (STEM) research project that focused on digital health. Methods: The evaluation was conducted with members of the project's Public Advisory Groups (PAG) and with researchers who had participated in involvement activities. Two questionnaires were designed based on a public involvement value systems and clusters framework. Results: Responses from members of the PAG (n = 10) were mostly positive towards normative values, which include moral, ethical and political aspects of involvement in research, and towards values concerning the conduct of public involvement and best practices. Researchers' responses (n = 16) indicated they felt that involvement was generally effective and increased the quality, relevance and generalizability of their work. However, their responses about the validity of involvement in research were varied. They also highlighted several challenges including how well public involvement impacted on research, how decisions made in the research might differ from the views generated from public involvement, and barriers to researchers' participation. Discussion and conclusion: Our evaluation suggests that members of the public and the researchers value involvement. However, there is a need to consider how to embed public involvement to an even greater extent in STEM contexts and a need to address any barriers for researchers' own involvement.